Avaliação numérica de alvenaria estrutural devido a cargas dinâmicas - Lima, Athila Vieira (2024)
This study presents a detailed analysis of the behavior of masonry walls under cyclic horizontal loads, focusing on the influence of different vertical pressures, displacement amplitudes, and opening geometries. Using numerical simulations, hysteresis curves and analyses of tensile and compressive damage are obtained for various models. The results show that the application of vertical pressure enhances wall confinement, delaying crack onset and increasing initial stiffness. Larger cyclic displacement amplitudes result in greater energy dissipation but also led to higher structural stiffness degradation. The shape and size of the openings significantly influenced stress distribution and crack formation, with horizontal openings showing better structural performance compared to vertical openings. The conclusions of this study provide important guidelines for the reinforcement and design of masonry walls under cyclic loads. Comparisons with experimental data, such as the tests by Deng et al. (2023), demonstrated good representativeness of the crack pattern in the numerical models, validating the adopted approach.